Corrosivity and leaching behavior of controlled low-strength material (CLSM) made using bottom ash and quarry dust - Naganathan, S.; Razak, H.A.; Hamid, S.N.A. (2013)
This paper reports the corrosivity and leaching behavior of CLSM made using two different industrial wastes i.e. bottom ash from an incineration facility and quarry dust. The leachate samples were derived from fresh and hardened CLSM mixtures, and studied for leaching and electrical resistivity. The release of various contaminants and the consequent environmental impact caused by the contaminants were studied by the measurement of contaminants in the bleed, in the leachate at 28 days, and on the leachate derived from crushed block and whole block leaching done over a period of 126 days. Results indicated that the CLSM mixtures are non corrosive; diffusion was the leaching mechanism; and the contaminants were found to be moderate to low mobility. Â© 2013 Elsevier Ltd.